Determination of Type and Concentration of Electrolyte Solution on the Basis of Analysis of Potentiodynamic Curves - R. I. Vorobey; O. K. Gusev; V. P. Kiryeenko; A. K. Tyavlovsky; K. L. Tyavlovsky; V. B. Yarzhembitsky (Наука и техника)
The paper shows the results of experimental investigation of non-stable regimes of excitation of electrode system of conductivity measuring cell. The analysis of experimental data based on existing theory of electrode processes has been made. The interpretation of non-conventional results concerning the dependence of conductivity measuring cell current on voltage excitation has been given. It has been shown that with certain parameters of excitation potentiodynamic curves significantly differ for various types of solutions (in particular for acid and alkali media) that makes it possible to use the regime of analysis of these curves for determination of type and concentration of a solution. Operational diagram of the device using the detected effect is given in the paper.